A comparison between oral chemotherapy combined with radiotherapy and radiotherapy for newly diagnosed glioblastoma: A systematic review and meta-analysis. Issue 44 (November 2017) - Wang, Zhuo; Yang, Guozi; Zhang, Yu-Yu; Yao, Yan; Dong, Li-Hua
Abstract : Abstract: The prognosis of glioblastoma (GBM), a major subtype of grade IV glioma, is rather poor nowadays. The efficiency of chemotherapy serving as the adjunct to radiotherapy (RT) for treating GBM is still controversial. In this study, we aim to investigate the overall survival (OS) and progression-free survival (PFS) in patients with newly diagnosed GBM received RT plus chemotherapy or with RT alone. Literatures were searched from the PubMed, Embase, and Cochrane Library between January 2001 and June 2015. Study selection was conducted based on the following criteria: randomized clinical trial (RCT) of adjuvant RT plus chemotherapy versus RT alone; studies comparing OS and/or PFS; and studies including cases medically confirmed of newly diagnosed GBM. Five RCTs (1655 patients) were eligible in this study. The meta-analysis showed a significant improvement in OS of patients treated with RT plus oral chemotherapy compared with that of RT alone (hazard ratio 0.70; 95% confidence interval, 0.56–0.88, P  = .002). Adjuvant chemotherapy confers a survival benefit in patients newly diagnosed with GBM.